Judah and the Judeans in the Persian Period: [conference, "Judah and the Judeans in the Achaemenid period", that took place in Heidelberg on 15 - 18 July, 2003] - Lipshits, ʿOded; Oeming, Manfred (Eisenbrauns, 2006)
Pt. 1. Historical, epigraphical, and archaeological perspectives -- pt. 2. Biblical perspectives